Food safety in developing countries - Grace, Delia; Unger, Fred; Lapar, Ma. Lucila; Hung Nguyen-Viet (2015)
Evidence on foodborne disease (FBD) in developing countries is still limited, but important studies in recent years have broadened our understanding. These suggest that developing country consumers are concerned about FBD; that most of the known burden of FBD disease comes from biological hazards; and, that most FBD is the result of consumption of fresh, perishable foods sold in informal markets. FBD is likely to increase in developing countries as the result of massive increases in the consumption of risky foods (livestock and fish products and produce) and lengthening and broadening value chains. Although intensification of agricultural production is a strong trend, so far agroindustrial production and modern retail have not demonstrated clear advantages in food safety and disease control. There is limited evidence on effective, sustainable and scalable interventions to improve food safety in domestic markets. Training farmers on input use and good practices often benefits those farmers trained, but has not been scalable or sustainable, except where good practices are linked to eligibility for export. Training informal value chain actors who receive business benefits from being trained has been more successful. Such benefits may include prime sell prices for niche or branded products or increased consumer trust. New technologies strongly driving by their feasibility, growing public concern and increased emphasis on food system governance can also improve food safety. Promising examples from ongoing ILRI research (e.g. Uganda, Slaughterhouses hygienic management and Vietnam, Food Safety task force) will be provided and discussed.